Electrochemical Friedel–Crafts-type amidomethylation of arenes by a novel electrochemical oxidation system using a quasi-divided cell and trialkylammonium tetrafluoroborate - Hisanori Senboku; Mizuki Hayama; Hidetoshi Matsuno (Beilstein Journal of Organic Chemistry, 2022)
Electrochemical Friedel–Crafts-type amidomethylation was successfully carried out by a novel electrochemical oxidation system using a quasi-divided cell and trialkylammonium tetrafluoroborates, such as iPr2NHEtBF4. Constant current electrolysis of 1,3,5-trimethoxybenzene or indoles in DMA containing 0.1 M iPr2NHEtBF4 using an undivided cell equipped with a Pt plate cathode and a Pt wire anode (a quasi-divided cell) resulted in selective formation of N-acyliminium ions of DMA at the anode, which reacted with arenes to give the corresponding amidomethylated products in good to high yields.